Skrining Aktivitas Antibakteri Ekstrak Etanol 70% Dari Beberapa Daun Tanaman Di Indonesia Terhadap Bakteri Shigella sonnei Serta Bioautografinya - Utari, Selvy Sekti Noor, Rima Munawaroh, M.Sc., Apt (2016)
The frequency of occurrence of diarrhea in developing countries more 2-3 times compared with developed countries. Shigella sonnei is a typical of Gram-negative bacterium as the major cause of diarrhea and shigellosis. Shigella has caused approximately 10% of acute diarrhea in children, and 12% in adult. Several leaves of plants used for this research are sembukan, tamarind, gandola or binahong, spider lily leaves, guava, marigolds, fragrant pandan, moringa, patchouli and beluntas. The purpose of this research was to determine the antibacterial activity, the highest antibacterial activity and the classes of compounds that play role on the antibacterial activity of 70% ethanol extract of few leaves plantation in Indonesia. The extraction of the few leaves was done by using maceration method. The results of extraction were tested on Shigella sonnei bacteria by using Kirby Bauer diffusion method with 20% concentration at 15 mL/disk. The detection of compounds was done by using phytochemical screening and Thin Layer Chromatography (TLC) with a stationary phase of silica gel GF254 and mobile phase B: A: W (4: 1: 5 v/v/v) upper phase followed by a bioautografi test by using bioautografi contact. Guava leaf (Psidium guajava L) having an average inhibitory zone of 10.7 ± 0.6 mm and gandola or binahong leaf (Basella alba L) having an average inhibitory zone of 6,3 ± 0,3 mm. The results of phytochemical screening and TLC indicated any tannins, saponins, terpenoids and flavonoids in etanol extract of guava. The result of bioautografi test indicated that compounds which play role as antibacterial activity are saponins, flavonoids and tannins.